2010
DOI: 10.3989/gya.108709
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and seasonal variation of the quality of virgin olive oil of the Throumbolia and Koroneiki varieties from southern Greece

Abstract: RESUMEN Caracterización y variación estacional de la calidad del aceite de oliva virgen de las variedades Throumbolia y Koroneiki del Sur de Creta.Aceite de oliva virgen extra fue producida con aceitunas de las dos principales variedades cultivadas en la región de Rethymnon en la isla de Creta denominadas "Throumbolia" y "Koroneiki". La primera es una variedad muy famosa debido a la falta de amargor natural de su fruto, mientras que la última es la variedad más común de aceitunas cultivada en el norte de Greci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
68
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 29 publications
16
68
0
2
Order By: Relevance
“…To corroborate this, the correlation between these parameters gave high coefficients, one of the highest corresponding to oleic and linoleic acid (r = −0.94). Similar results were obtained by other researchers (Vekiari et al, 2010). Gracia et al (2009) showed values of oleic acid of 68.9% and 11.6% of linoleic acid in the "Arbequina" variety.…”
Section: Fatty Acid Compositionsupporting
confidence: 91%
See 2 more Smart Citations
“…To corroborate this, the correlation between these parameters gave high coefficients, one of the highest corresponding to oleic and linoleic acid (r = −0.94). Similar results were obtained by other researchers (Vekiari et al, 2010). Gracia et al (2009) showed values of oleic acid of 68.9% and 11.6% of linoleic acid in the "Arbequina" variety.…”
Section: Fatty Acid Compositionsupporting
confidence: 91%
“…On the other hand, Salvador et al (2001) studied the "Cornicabra" variety and they obtained values of 80.8% and 4.66% of oleic and linoleic acids, respectively, which are higher than those obtained in this assay. Also, Vekiari et al (2010) found a linoleic/linolenic relationship similar to that obtained in this study with a ratio of 17 approximately. Note the importance of this relationship in nutrition because nowadays it is considered that a moderate contribution of linoleic acid is suitable to the current trends of a healthy diet.…”
Section: Fatty Acid Compositionsupporting
confidence: 88%
See 1 more Smart Citation
“…Sterol composition in olive oil is affected by cultivar, crop year, geographic factors, degree of fruit ripeness, storage time of fruits prior to oil extraction, and processing (Boskou et al, 2006). The cultivars with the highest Δ 5 -avenasterol content are Koroneiki (23.9%) (Vekiari et al, 2010), Arbequina (23.2%) (Gracia et al, 2009), and Leccino (21.4%) (Gül and Seker, 2006). Accordingly, the high Δ 5 -avenasterol levels in the selection UC-I-2-35, observed in both years of the experiment (Figure 1), are exceptional within olive oil cultivars.…”
mentioning
confidence: 82%
“…Results are not in agreement with others who noticed a clear impact on year over cultivar (Gracia et al 200) probably due to the fact that we were looking just to one cultivar and we considered only acidity, K and peroxide index. In fact, differences among cultivars are more evident when volatiles, fatty acids and sterol composition are considered (Vekiari et al 2010). …”
Section: Electronic Sensory Analysismentioning
confidence: 99%